Academic and social impact assessment on university graduates - González, Gabriel; Díez-Echavarría, Luisa; Zapa, Elkin; Eusse, Danilo (Revista Complutense de Educación, 2019)
Higher education institutions should educate their students according to the requirements of the context in which they act, because according to their performance, it will be measured if the socioeconomic development policies are effective. Then, it is necessary to identify the impact of education on its graduates, and make necessary adjustments that generate continuous improvement. The objective of this article is to estimate the academic and social impact of graduates of Instituto Tecnológico Metropolitano – Medellín, through a multivariate analysis and the estimation of the Average Treatment Effect (ATE) model. It was found that education offered to this population has generated an academic impact, associated to the updating studies, and two social impacts, associated to the labor situation and income level perceived by graduates. It is recommended to use this methodology in other institutions, since it usually yields more informative and accurate results than the traditional characterization studies, and it can be measure the effect of any strategy.
Keywords: Curriculum; university studies; university graduates; academic impact; social impact